A Comparative Study of Seismic Performance Evaluation of Reinforced Concrete Frame Structures Using Chinese and African Seismic Codes - Musaab Suliman; Liang Lu (Advances in Civil Engineering)
The evaluation of various earthquake codes, it is one of the significant challenges in the study area of earthquake engineering. However, according to the literature review, most research works have not addressed comparing Chinese and African seismic codes. Therefore, the purpose of this study is to identify each code’s advantages by comparing assessment of the seismic efficacy of moment resistance frame reinforced concrete (MRF-RC) frames using four different codes: the Ethiopian Building Code Standard (EBCS-8), the Egyptian Code for Design and Construction of Reinforced Concrete Structures (ECP-201), the Algerian Seismic Regulations (RPA-99), and the Chinese Code for Seismic Design of Buildings (GB-50011), the first three are the major codes used in Africa. The seismic provisions of these codes are compared and evaluated using nonlinear time-history analysis (NL-THA) and nonlinear static pushover to validate the results. These analyses are performed on four MRF-RC frame models with different heights. The results include various parameters that reflect the seismic performance of the structures. The study revealed that the Chinese code is more conservative and overestimates seismic performance compared with African codes. However, the Chinese code can be applied in African projects considering the African soil classifications, and seismic weight are adjusted to meet the African design criteria.